Dharma Pawayangan: Transliteration, Translation, And Cultural Values Analysis - I Nengah Duija; Ni Made Ayu Susanthi Pradnya Paramitha (Jayapangus Press, 2022)
As time changes, the Balinese wayang (shadow puppet show) performances has undergone changes marked by the emergence of new plays. This study examines the lontar (traditional scripture) of Dharma Pawayangan through a manuscript study since the Dharma Pawayangan Lontar contains information and instructions on traditional puppetry art which can be used as the basis for aesthetic understanding of Balinese puppeteers today. To avoid being crushed by the secularization of new wayang creation, thus resulting in the retainment of its religio-magic nature. This study aims to determine the transliteration and translation of Dharma Pawayangan B text, and its cultural values. Another goal is to produce puppetry literary texts that are a source of inspiration for Balinese puppet masters. The result of this research is the Dharma Pawayangan B, transliterated into Latin characters and translated into Indonesian. This manuscript contains information on puppets, puppetry, and the aspects that must be understood by the dalang, namely kiwa tengen, ethics, taboos, equipment, theology, rituals, and punishment for violation of the rules, as well as the development of wayang in the modern era.